Fluorescent graphitic carbon nitride and graphene oxide quantum dots as efficient nanozymes: Colorimetric detection of fluoride ion in water by graphitic carbon nitride quantum dots. Issue 1 (February 2021) - Devi, Mamta; Das, Punamshree; Boruah, Purna K.; Deka, Manash J.; Duarah, Rituparna; Gogoi, Abinash; Neog, Dipankar; Dutta, Hemant S.; Das, Manash R.
Graphical abstract: Highlights: Fluorescent g-CNQDs and GQDs are synthesized using simple cost-effective method. Peroxidase mimic activity of prepared g-CNQDs and GQDs (nanozymes) were established. A simple colorimetric system is established for ultrasensitive detection of fluoride ions. High sensitivity and selectivity of g-CNQDs for fluoride ions detection with LOD of 0.53 mg/L. Abstract: Development of strategies based on artificial nanozymes over natural enzymes for sensing of toxic ions in water has drawn tremendous interest among researchers. Herein, we have reported a facile synthesis of fluorescent graphitic carbon nitride quantum dots (g-CNQDs) and graphene oxide quantum dots (GQDs) using simple, cost-effective and low-temperature methods from readily available precursors such as urea, trisodium citrate, and citric acid. The peroxidase mimic activity of prepared g-CNQDs and GQDs (nanozymes) were established without functionalizing or doping with other nanoparticles. These nanozymes acted as efficient catalysts, facilitating the simultaneous reduction of H2 O2 and oxidation of colorless peroxidase substrate 3, 3′, 5, 5′- tetramethylbenzidine (TMB) to produce a blue color oxidized TMB in presence of H2 O2 . Thus, a simple colorimetric system is established based on the enzyme mimic activity of the synthesized g-CNQDs for detection of fluoride ions in aqueous solution. The g-CNQDs showed high sensitivity and selectivity towards the detection of fluoride ions in water with a detection limit 4.06 μM in a wide detection range upto 120 μM. This study provides the evidence that the reported colorimetric technique is green, economic, fast responsive, sensitive, and highly selective which can be further utilized for the detection of fluoride ion in naturally occurring water samples.